Lacustrine geoarchaeology in the central Kalahari: implications for Middle Stone Age behaviour and adaptation in dryland conditions - Thomas, DSG; Burrough, S; Coulson, S; Mothulatshipi, S; Nash, DJ; Staurset, S (Elsevier, 2022)
The Middle Stone Age (MSA) was a time of great human adaptation and innovation. In southern Africa, coastal locations have been viewed as key places for the development of human resource use and behaviour, with the dryness of the continental interior after c.130 ka regarded as both an obstacle to occupation and a limit on behaviour. Newly excavated MSA sites on the floor of the now-dry palaeolake Makgadikgadi basin, central Botswana, along with accompanying environmental data, have provided a significant opportunity to reassess the nature of MSA adaptation to, and behaviour under, dry conditions. Excavated sites dated to 80–72 ka and post 57 ka reveal purposeful early human use of an extensive 60,000 km2 lacustrine basin during dry, as opposed to lake-high, phases, as well as highlighting movement strategies for tool-making resource procurement. Findings have significant implications for theories of early human mobility and innovation, as well as for understanding the drivers, constraints and opportunities for the use of drylands. The deliberate selective movement of lithic raw materials within the basin for artefact manufacture evidences thoughtful adaptation to dry conditions within the lake basin. This research shows that open-air sites in the Kalahari drylands of central southern Africa can make important contributions to debates surrounding the development of human-environment relationships during the MSA, as well as challenging narratives of a hostile and largely empty landscape.